Sectoral growth rates of the Nigerian economy - Vielrose, Egon (Ibadan (Nigeria) : Nigeria institute of social and economic research university of Ibadan)
This contains the data concerning Gross Domestic Product (GDP) and its components since 1950.
ahz 14/03/2019
Loans
Keywords: Economic Development; Nigeria